Frankfurters made with pork meat, emmer wheat (Triticum dicoccum Schübler) and almonds nut (Prunus dulcis Mill.): evaluation during storage of a novel food from an ancient recipe. (November 2018) - Ranucci, David; Miraglia, Dino; Branciari, Raffaella; Morganti, Giulia; Roila, Rossana; Zhou, Kang; Jiang, Haiyang; Braconi, Paolo
Abstract: The physical, chemical and microbiological characteristics of reformulated meat-based frankfurters, derived from an ancient Roman cookbook and produced from pork meat, emmer wheat, almond, fish sauce and spices, were investigated during storage. Two different formulations were considered, with pork thigh and pork shoulder muscles, respectively. The products contain 13–16% protein, 14–19% fat, 14% carbohydrates, >7% fibre and a polyunsaturated/saturated fatty acids ratio above 0.4. During the 24 days of storage, both products evidenced a decrease in the pH and increases in the total volatile nitrogen content and TBARs value, whereas, the a w remained stable. From a microbiological perspective, increases in the total viable count and lactic acid bacteria up to 4.8 log cfu/g occurred during storage, but no pathogens were found. Sensory analyses revealed a change in odour and flavour at 18 days, with the detection of a fermented and rancid taste. Survival sensory analysis defined a shelf life of the products of between 18.6 and 22.7 days. Highlights: Quality traits of frankfurters derived from ancient Roman cookbook were evaluated. The major ingredients of the frankfurters were pork meat, emmer wheat and almonds. High fibre content was due to emmer wheat and almonds. Oxidation and fermentation occur during storage. The sensory shelf life of the frankfurters was between 19 and 23 days.